2008
DOI: 10.1179/174328407x213215
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grain size fluctuations on ductility of superplastic magnesium alloys processed by severe plastic deformation

Abstract: The influence of fluctuations in the grain size along the gage length on ductility is analyzed in the superplastic regime. It is demonstrated that these fluctuations produce a similar effect to that produced by variations in the initial uniformity of the sample, leading to premature necking. In order to reach superplastic elongations of 400%, fluctuations in grain size of less than 0.5% between two zones of the gage length are required. As an example, the superplastic behavior of an AZ61 alloy, processed by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In order to achieve the better mechanical properties of the superplastic alloy, the alloys should possess fine grain size and it should remain stable during deformation [50]. A fine-grained microstructure has a greater number of grains and grain boundaries than that of a coarse grain counterpart and is typically less than 10 µm.…”
Section: Effect Of Initial Grain Size On the Superplasticity Of Al Almentioning
confidence: 99%
“…In order to achieve the better mechanical properties of the superplastic alloy, the alloys should possess fine grain size and it should remain stable during deformation [50]. A fine-grained microstructure has a greater number of grains and grain boundaries than that of a coarse grain counterpart and is typically less than 10 µm.…”
Section: Effect Of Initial Grain Size On the Superplasticity Of Al Almentioning
confidence: 99%
“…Microstructural evolution during ECAP of magnesium and its alloys has been a subject of numerous investigations …”
Section: Microstructure Evolution During Spd Of Magnesium Alloysmentioning
confidence: 99%
“…Under these conditions, the significance of DRX for microstructure formation during hot deformation processing of Mg alloys cannot be overvalued. The DRX mechanisms in magnesium and its alloys have been extensively studied and understood in great details . For additional information, the reader is directed to a recent comprehensive review by Kaibyshev .…”
Section: Microstructure Evolution During Spd Of Magnesium Alloysmentioning
confidence: 99%
“…An iso-strain model, considering that each grain deforms at the imposed macroscopic strain rate, allows the ma- jor experimental observations to be readily explained and predicted. The influence of large-scale heterogeneities in the grain size on ductility was also analysed in the superplastic regime [111]. It was demonstrated that these fluctuations could lead to premature necking.…”
Section: High Temperature Deformationmentioning
confidence: 99%
“…In addition, the thermal stability of the microstructures obtained by severe plastic deformation processes has been discussed with the aim of obtaining the optimum superplastic conditions [67,109]. Finally, the effect of microstructural heterogeneities on the superplastic capability of the magnesium alloys has been analysed and modelled [110,111]. Determination of steady-state stress data at high temperature for a given set of strain rates under the condition of constant microstructure is difficult, as significant microstructural changes (grain growth, texture changes) take place during testing.…”
Section: High Temperature Deformationmentioning
confidence: 99%